2016
DOI: 10.1111/ina.12275
|View full text |Cite
|
Sign up to set email alerts
|

Allergy and respiratory health effects of dampness and dampness-related agents in schools and homes: a cross-sectional study in Danish pupils

Abstract: Little is known about the health effects of school-related indoor dampness and microbial exposures. In this study, we investigated dampness and dampness-related agents in both homes and schools and their association with allergy and respiratory health effects in 330 Danish pupils. Classroom dampness was identified based on technical inspection and bedroom dampness on parents' self-report. Classroom and bedroom dust was analyzed for seven microbial components. Skin prick testing determined atopic sensitization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 54 publications
0
35
1
Order By: Relevance
“…For younger children, exposure to dust mites and molds in day care centers was associated with wheezing [23]. Likewise, researchers in Denmark found that high classroom dampness was associated with increased wheezing and decreased spirometry in exposed students [24]. Finally, mold exposure in school classrooms was shown to be significantly associated with current asthma symptoms and asthma symptoms that improved over holidays and weekends when the students were out of school [25 ▪▪ ].…”
Section: Away From Home: Exposure To Indoor Allergens In Other Childhmentioning
confidence: 99%
“…For younger children, exposure to dust mites and molds in day care centers was associated with wheezing [23]. Likewise, researchers in Denmark found that high classroom dampness was associated with increased wheezing and decreased spirometry in exposed students [24]. Finally, mold exposure in school classrooms was shown to be significantly associated with current asthma symptoms and asthma symptoms that improved over holidays and weekends when the students were out of school [25 ▪▪ ].…”
Section: Away From Home: Exposure To Indoor Allergens In Other Childhmentioning
confidence: 99%
“…The health data are entirely self-reported, and the occupants of damp and/or moldy schools may have been aware of the problems and their potential to cause health effects. 10,11,21,24,32,34,37,39,40 Four of the eight studies reported statistically significant worsening of one or more objective health outcomes with indicators of building dampness or mold. Four studies described in five papers assessed whether renovations to correct dampness and mold problems in schools improved health.…”
Section: Discussionmentioning
confidence: 99%
“…For dermal symptoms and current asthma, only four studies provided data. [33][34][35][36][37] One of the seven studies reported a very small statistically significant decrease in wheeze with higher airborne mold 38 and another study 24 reported a decrease in atopic dermatitis with higher airborne mold. The possibility of publication bias is always a concern for re- Data from studies not included in the meta-analyses were also reviewed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RIPC consisted of 3 occlusion-reperfusion cycles. The spinal cord I/R injury was conducted by the previously described technique [18]. Briefly, rats were anesthetized by 4% sodium pentobarbital (50 mg/kg, intraperitoneally).…”
Section: Methodsmentioning
confidence: 99%